Impact of mandibular 4-implant overdenture base construction techniques on assessment of occlusion with digital occlusion analysis system (clinical crossover study) - Ahmed Ali Abdelghany; Mohammed M. Fouad; Radwa Mohsen Kamal Emera; Osama Askar; Ayman Ahmed Mustafa Yaseen (BMC Oral Health)
Abstract Background Occlusion plays a crucial role in the long-term success and prognosis of implant-supported overdentures. The method used to fabricate the overdenture base, whether conventional or CAD/CAM milled, could influence occlusal contact balance. However, definitive evidence on this matter remains lacking. Thus, this study aimed to compare two fabrication techniques, CAD/CAM milled and conventional, for four-implant-supported complete mandibular overdenture bases, with a specific focus on their impact on occlusal balance. Methods Edentulous patients participated in this study received four-implant supported mandibular overdentures constructed using two different types of overdenture bases: CAD/CAM milled and conventional bases. A total of 21 patients, representing 42 overdentures, were enrolled in the study. Occlusal adjustments were made for each overdenture after picking up of attachments. The patients were classified randomly and equally into two groups: Group I: patients delivered maxillary complete dentures opposed to four implant-supported mandibular overdentures constructed with CAD/CAM milling followed by conventionally constructed dentures. Group II: patients delivered maxillary complete dentures opposed to four implant-supported mandibular overdentures constructed with conventional method followed by CAD/CAM milled dentures. According to the type of denture bases, dentures were classified into two equal groups: Group A: CAD/CAM constructed overdenture bases. Group B: conventionally constructed overdenture bases. For each overdenture group, occlusal analysis measurements were recorded at overdenture delivery (T0) and after three months of denture wearing (T3). Data was analyzed using the Statistical Package of Social Science (SPSS) program. Repeated measures ANOVA were used to test significant differences in occlusal force distribution between observation intervals, groups and locations followed by Bonferroni post hoc test for multiple comparisons. Independent samples t-test was used to compare occlusal force between groups. P is significant if < 0.05 at confidence interval 95%. Results Comparing different occlusal contact locations in each group at (T0) showed a significant difference between anterior and posterior locations whereas comparing different occlusal contact locations in each group at (T3) showed a significant difference between molar and premolar locations for group B while insignificant between molar and premolar locations for group A. The comparison between different intervals within group A revealed insignificant differences while significant occlusal changes at premolar and molar regions were presented within group B. Conclusions The four implant-supported CAD/CAM milled overdenture bases offer greater advantages over conventional ones in terms of occlusal contact stability. Clinical Trial Registry Number (NCT06080815))08/10/2023).